2004
DOI: 10.1007/s00540-004-0263-3
|View full text |Cite
|
Sign up to set email alerts
|

Dose-finding study of intravenous midazolam for sedation and amnesia during spinal anesthesia in patients premedicated with intramuscular midazolam

Abstract: For sedation and amnesia of the patients aged 20-50 years in spinal anesthesia with about 1 h duration receiving intramuscular midazolam 0.06 mg.kg(-1) as a premedication, intravenous midazolam 0.02 mg.kg(-1) might be effective and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
1
1
0
2
Order By: Relevance
“…[20] In another research conducted in Japan by Nishiyama et al on 20-25 years old patients, midazolam as a premedication was administrated and they concluded that "receiving IM midazolam 0.06 mg/kg 1 h before operation as a premedication following IV midazolam 0.02 mg/kg might be effective and safe." [21] This finding and this dosage is concomitant with our result although the studied population is different with our study.…”
Section: Discussionsupporting
confidence: 84%
“…[20] In another research conducted in Japan by Nishiyama et al on 20-25 years old patients, midazolam as a premedication was administrated and they concluded that "receiving IM midazolam 0.06 mg/kg 1 h before operation as a premedication following IV midazolam 0.02 mg/kg might be effective and safe." [21] This finding and this dosage is concomitant with our result although the studied population is different with our study.…”
Section: Discussionsupporting
confidence: 84%
“…[16] Midazolam im uygulamalarında sedasyon etkisi 15 dakikada başlamakta ve yaklaşık 60 dakika sürmektedir. [17] Propofol analjezik etkisi olmayan, sedasyonda da kullanılabilen nonopioid intravenöz anestezik ilaç-tır. [18] Bizim çalışmamızda, IHNB uygulanan hastaların yaklaşık yarısında ameliyatta sedasyon gereksinimi olmuştur.…”
Section: Discussionunclassified
“…Hareketle VAS değerleri arasında fark bulunmamış-tır. Hastanede kalış süresi SA+IHNB+cerrahi yara infiltrasyonu grubunda SA grubuna göre (18 [14][15][16][17][18][19][20][21][22][23][24][25][26]ve 23 [17][18][19][20][21][22][23][24][25][26] saat, ortanca [min-maks]) daha kısa gözlenmiştir. Sonuçta SA+IHNB+%0.75 ropivakain ile cerrahi yara yeri infiltrasyonunun ameliyat sonrası ilk üç saat ağrıyı azalttığını ve hastanede kalış süresini kısalttığı belirtilmektedir.…”
Section: Discussionunclassified
“…In our operating rooms (ORs), midazolam and butorphanol are used as a sedative or analgesic, respectively, in relatively healthy patients, expecting an amnesic effect in the former drug and a ceiling effect on respiratory depression in the latter drug. [9,10]. Of these drugs, however, there are many other reports supporting the superiority of midazolam [1,2,5,6,11,12].…”
Section: Introductionmentioning
confidence: 93%